Therapeutic effect of Duhuo Jisheng Decoction add-on Tui-na manipulation on osteoarthritis of knee: a randomized controlled trial - Kin Ho Chan; Jessica Y. L. Ching; Kam Leung Chan; Hoi Yi Lau; Ka Man Chu; Kenny Chan; Hon Fai Pang; Lok Chi Wong; Chon Pin Chia; Hong Wei Zhang; Tianhe Song; Sin Bond Leung; et al. (BMC, 2023)
Abstract Background Knee osteoarthritis (KOA) is a common degenerative joint condition that causes disability and pain in the elderly population. The prevalence of KOA among persons aged 63 or above is approximately 30%. Previous studies have reported the positive effects of Tui-na treatment and the Chinese herbal formula Du-Huo-Ji-Sheng Decoction (DHJSD) for KOA treatment. The current study aims to evaluate the add-on therapeutic effect of oral administration of DHJSD on KOA in addition to Tui-na. Methods We conducted a prospective, randomized, controlled clinical trial. Seventy study subjects with KOA were randomly assigned to the treatment and control groups in a 1:1 ratio. Both two groups received eight sessions of Tui-na manipulation for 4 weeks. The DHJSD was only administered to the study subjects in the treatment group. The primary outcome measure was rated using the WOMAC at the end of treatment (4 weeks). Secondary outcomes were assessed using EQ-5D-5L, a health-related quality of life with 5-level EQ-5D version at end of treatment (week 4) and follow-up (week 8). Results No statistically significant difference was found between two groups on WOMAC scores at the end of treatment. The mean WOMAC Pain subscale score was significantly lower in the treatment group than control group at week 8 follow up (mean difference, MD − 1.8, 95% CI − 3.5 to − 0.02, P = 0.048). The mean WOMAC Stiffness subscale score was significantly lower in the treatment group than in the control group at week 2 (MD 0.74, 95% CI 0.05 to 1.42, P = 0.035) and week 8 follow up (MD 0.95, 95% CI 0.26 to 1.65, P = 0.008). The mean EQ-5D index value was significantly improved in the treatment group than in the control group at week 2 (MD 0.17, 95% CI 0.02 to 0.31, P = 0.022). The analysis of WOMAC scores and EQ-5D-5L in both groups showed statistically significant improvement with time. No significant adverse effect was found during the trial. Conclusion DHJSD may have an add-on effect in addition to Tui-na manipulation relieving pain and improving stiffness as well as quality of life (QOL) in patients with KOA. The combined treatment was generally safe and well tolerated. Trial registration The study was registered at the ClinicalTrials.gov (website: https://clinicaltrials.gov/ct2/show/NCT04492670 , registry number: NCT04492670), registered on 30 July 2020.